Grievances or skills? The effect of education on youth political participation in Egypt and Tunisia. Issue 2 (March 2022) - Pellicer, Miquel; Assaad, Ragui; Krafft, Caroline; Salemi, Colette
The educated have figured prominently in protests and elections in several Middle East and North Africa (MENA) countries. The dominant explanation for this pattern centers on grievances and unfulfilled aspirations due to low education returns in the MENA. However, the pattern may simply reflect the unequal participation observed in many democracies where education provides skills and resources that facilitate political participation. This article compares the roles of skills and grievances in explaining the relationship between education and youth political participation during and after the Arab Spring. We use youth surveys with detailed data on education and political participation from Egypt and Tunisia. We control for parental education and family background to partially account for the potential of background to drive the education and participation relationship. Overall, our results are consistent with the skill channel and lend little support to the grievance channel. Our findings raise concerns about the exclusion of uneducated youth from both unconventional and conventional political participation in MENA politics.